Cyber Security Ventures: An Assessment of Entrepreneurial Opportunities in Protecting Digital Assets in Nigeria - Zubair Shaib Bashir; Marcus Garvey Orji (Rowter Journal, 2025)
The cybersecurity industry is experiencing unprecedented growth due to increasing digitalization and rising cyber threats. This study investigates entrepreneurial opportunities and key success factors for cybersecurity startups in Nigeria, emphasizing innovation in protecting digital assets. Using a quantitative survey design, data was collected from 100 cybersecurity professionals, entrepreneurs, and investors to explore the dynamics of this fast-evolving sector. The findings highlight opportunities to leverage emerging technologies, such as artificial intelligence (AI), blockchain, and the Internet of Things (IoT), to address challenges like cybercrime, data breaches, and IoT vulnerabilities. Significant barriers, including regulatory compliance, high capital requirements, and a shortage of skilled professionals, were identified. Key success factors include technological innovation, talent acquisition, and strategic partnerships. Collaboration with investors is crucial for overcoming challenges and fostering sustainable growth. The study provides actionable insights for entrepreneurs, investors, and policymakers to navigate the complexities of the cybersecurity market. It concludes that adaptability, innovation, and collaboration are critical for startups to thrive. Addressing market demands and mitigating challenges can position cybersecurity ventures to significantly enhance digital asset protection in an interconnected world.